IMPLEMENTASI MEDIA KARTU HURUF DALAM MENSTIMULASI KEMAMPUAN MENGENAL HURUF PADA KELOMPOK B TK PERMATA BUNDA - Nurhayati, Nurhayati; Rini, Ratu Yustika; Sari, Novita (Jurnal Anak Bangsa, 2025)
This research aims to examine the implementation of the use of letter cards in stimulating the ability to recognize letters in group B at Permata Bunda Kindergarten. Recognizing letters in early childhood is one of the basic skills that is very important in supporting children's cognitive development and literacy abilities. One medium that can be used to improve the ability to recognize letters is by using letter cards. The subjects in this research were 22 children from group B at Permata Bunda Kindergarten. Data was obtained from observation, interviews and documentation. The results of the research show that the use of letter cards significantly increases children's ability to recognize letters compared to conventional methods. Children who are taught using letter cards recognize the letters of the alphabet more quickly and show a higher interest in learning. Apart from that, using letter cards also has a positive impact on children's fine motor skills and communication abilities.